INFLUENCE OF ETCHING STRATEGY ON THE ADHESIVE INTERFACE MEDIATED BY A UNIVERSAL BONDING SYSTEM - Gianina Iovan; Simona Stoleriu; Cristina-Angela Ghiorghe; Sorina Solomon; Irina Nica; Alexandru Iovan; Ionuț Tărăboanță; Sorin Andrian (Romanian Dental Association for Education, 2020)
The aim of the study was to evaluate the composite resin-tooth interface when using a universal adhesive applied in different etching strategies. Materials and method: 20 class V cavities were prepared in extracted teeth and restored with a composite resin using a universal adhesive system. Half of the restorations were applied using etch-and-rinse technique and the other half were applied with self-etch technique. The samples had been subjected to a dye penetration microleakage test and then the teeth were axially sectioned. The microleakage scores and the morphology of the adhesive joint were evaluated using an optical microscope and a scanning electron microscope. Results: The microleakage scores did not show a significant difference between the self-etch group and the total etch-group. For both groups, no significant gaps were noticed, however few cracks were visible within the adhesive layer. The SEM images showed the preservation of a tide contact between the composite resin and the dental tissues in most specimens of the both groups. An adhesive joint involving a layer of adhesive resin was formed between composite resin and both enamel and dentin regardless of the chosen technique (self-etch or total etch strategy). Conclusions: The immediate sealing qualities and the morphology of the interface did not significantly change when total etch strategy had been used when comparing to self-etch strategy.